Estudio de factibilidad para la creación de una sucursal del GOLD'S GYM, cantón Quevedo año 2014 - Basurto Tovar, Freddy Fabricio (2015)
This research was based on conduct a feasibility study to find the feasibility for the creation of a branch of Gold's Gym in the city of Quevedo. Currently the canton de Quevedo has a population 173,575 inhabitants which makes it attractive for establishing a business. To find the viability of the feasibility study was used to conduct four studies which are: market research, technical studies, economic analysis and financial study that will give them the information necessary for decision-making. Then we will present the findings in each study. By conducting market research conducted in the canton Quevedo, indicates that 44% of respondents said that people go to a gym for health, 87% also said that if you know the chain of gyms GOLD`S GYM With the feasibility study attempts were made to find the best location of the branch of GOLD`S GYM, leaving resulted in the city center between the 12th and streets Av. October 7, local physical space will feature 300 square meters on two floors being an area of sufficient space for the establishment of the business. The economic study was determined that for the setting up of the project is necessary to have an investment of $ 102,503.29, which will be funded at 100% for a bank loan of CFN to an interest rate of 10.5% at 5 years time. The project generated for the first year a profit of 70.593.05 increase for subsequent years With financial study was obtained that the project is feasible because the NPV is positive $ 507,156.08; IRR is 147% and the B / C ratio generate a profit of sixty cents for every dollar spent